Professional accounting skills in the digital age and the quality of financial reports of accountants in the gold star mill business - Pongsrirojana, Chomchamai (Journal of Roi Kaensarn Academi, 2024)
The objectives of this study were to 1) study the relationship between professional accounting skills in the digital age and the quality of financial reports of accountants in gold star-rated mill businesses. 2) study the qualitative characteristics of financial reports and apply them to Operating a gold star mill business. 3) Use the conclusions obtained from the accounting professional skills survey in the digital age to improve the quality of financial reports of the star mill business. Gold star type to be of higher quality. The sample group used in the research was 136 accountants who does accounting for the rice mill. The instrument used to collect data was a questionnaire and used statistics to analyze the data by finding percentages, means, and standard deviations. Correlation coefficient statistics and simple regression analysis statistics to test hypotheses. The results of the research found that 1) Accounting professional skills in the digital age and the quality of financial reports of business accountants with a gold star rating. There is a significant relationship in the same direction at the 0.01 level. 2) The basic qualitative characteristics of the overall financial report are at a high level. 3) Accounting professional skills in the digital age significantly affect the quality of the financial report level 0.01. Society will receive guidelines for developing the professional skills of accountants that should be driven by technological innovation leading to application in business operations. The gold star mill business has been successful. As well as gaining a new theoretical framework that is beneficial to the accounting profession.